Fat embolism syndrome with cerebral fat embolism through a patent foramen ovale: A case report - Yang, Lijuan (Medicine (Baltimore), 2020)
RATIONALE: Fat embolism syndrome with cerebral fat embolism, rarely observed at our neurology department, is often associated with long bone fractures. Its diagnosis is based on medical history and supportive imaging data and is usually not difficult. However, its pathogenesis remains poorly understood. PATIENT CONCERNS: A 46-year-old woman was urgently presented to a nearby hospital because of a femur fracture caused by an accident. She rapidly developed somnolence and was suspected to have fat embolism syndrome. DIAGNOSES: Due to patients history of trauma and supportive imaging data, she was diagnosed with fat embolism syndrome obviously. However, severe brain damage confused our understanding of the pathogenesis. The subsequent diagnosis of fat embolism syndrome with patent foramen ovale provided a reasonable explanation. INTERVENTIONS: Initially, we did not consider the fact that the patient had developed fat embolism syndrome and thus designed a comprehensive treatment program for fat embolism syndrome. Then the routine cardiac and vascular ultrasound screening were followed up, but patent foramen ovale was diagnosed unexpectedly, which led to a more aggressive treatment of brain injury. OUTCOMES: After relevant symptomatic treatment continued for nearly 3 months, an overall improvement was observed. Patients consciousness was restored but language disorders were left. LESSONS: Clinicians should consider patent foramen ovale as the embolization pathway, particularly in young and middle-aged patients with cerebral embolism because it is often mistaken for a rare situation.